AXES OF WORLD POWER IN THE 21ST CENTURY: AN ANALYTICAL PROPOSAL - Visentini, Paulo Fagundes (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The ranking of the hierarchy and grouping of World Powers is not based exclusively on material indicators such as economics, natural resources, territorial extension, population size and military resources. It is necessary to consider the stage in which the transformational process of the post-Cold War International System is, the position in which a power stands, and general and specific historical trends. The present article proposes a classification that identifies the existence of four axes of world power: 1) the Anglo-Saxon military-rentier; 2) the semi-sovereign industriallydeveloped; 3) the semi-peripheral industrially-emergent; and 4) the agrarian, mineral and demographic peripheral.